2012
DOI: 10.1111/j.1750-3841.2012.02922.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Clostridium perfringens Spore Germination and Outgrowth by Lemon Juice and Vinegar Product in Reduced NaCl Roast Beef

Abstract: Cooked, ready-to-eat meat products should be cooled rapidly to reduce the risk of Clostridium perfringens spore germination and outgrowth. Meat processors are reducing the sodium chloride content of the processed meats as a consequence of the dietary recommendations. Sodium chloride reduces the risk of C. perfringens spore germination and outgrowth in meat products. Antimicrobials that contribute minimally to the sodium content of the product should be incorporated into processed meats to assure food safety. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Spore germination is a necessary step in resuming vegetative growth; thus, the probability that the spores germinate in food products needs to be taken into account when assessing the risk of spoilage or outgrowth of pathogenic spore formers. Moreover, both inhibition of spore germination and induction of germination before inactivation treatments (which renders the spore sensitive) are used in the food industry to improve food safety (7)(8)(9)(10)(11)(12). However, none of these strategies is completely effective.…”
mentioning
confidence: 99%
“…Spore germination is a necessary step in resuming vegetative growth; thus, the probability that the spores germinate in food products needs to be taken into account when assessing the risk of spoilage or outgrowth of pathogenic spore formers. Moreover, both inhibition of spore germination and induction of germination before inactivation treatments (which renders the spore sensitive) are used in the food industry to improve food safety (7)(8)(9)(10)(11)(12). However, none of these strategies is completely effective.…”
mentioning
confidence: 99%
“…The cooling data contain both single‐ and dual‐rate cooling profiles. For most single‐rate cooling profiles, the temperature decreases exponentially from 54.4 to 7.2 °C or 4.4 °C in 6.5, 9, 12, 15, 18, and 21 h (Thippareddi and others ; Zaika ; Juneja and Thippareddi , ; Smith and others ; Smith and Schaffner ; Sánchez‐Plata and others ; Juneja and others , ; Olds and others ; Juneja and Friedman ; Velugoti and others ; Singh and others ; Li and others ; Decker and others ; Juneja and others ; Kennedy and others ; Redondo‐Solano and others ; King and others ). The single‐rate cooling profiles also include 2 linear cooling profiles from 54.4 to 7.2 °C (King and others ) and 5 customized cooling profiles (Olds and others ; Decker and others ).…”
Section: Methodsmentioning
confidence: 99%
“…Growth inhibition of C. perfringens also has been noted in beef patties at a level of 2 or 3% potassium lactate with no negative effects on the product's sensory aspects (6). Li et al (13) found that the addition of lemon juice and vinegar products inhibited C. perfringens spore germination and outgrowth. This research suggests that either organic acids or their neutralized salts have an effect on the germination and growth of C. perfringens spores.…”
mentioning
confidence: 99%